Checklist of the Cerambycidae (Insecta, Coleoptera) from central Bahia State (Brazil), with the description of two new species and new geographic records - Nascimento, Francisco E. De L.; Botero, Juan Pablo; Bravo, Freddy (Zootaxa, 2016)
A list of Cerambycidae species from three municipalities of central Bahia (Milagres, Maracás and Iaçu) is presented. A total of 108 species are registered, 17 of which are new geographical records for the state, are listed, including two new species of Aerenicini (Lamiinae), Suipinima flavumtuberculata sp. nov. and Aereniphaula bandana sp. nov. which are described and illustrated. A key to the species of Suipinima and taxonomic notes on Suipinima eccentrica (Galileo & Martins, 1992) are provided.